Association between occupational stress and lifestyle factors with metabolic syndrome among nurses in Ahvaz City, Iran - Salimi, Mahin (2013)
Despite the fact that metabolic syndrome is an important health concern among nurses, very little research has examined metabolic syndrome and the contributing factors to its development in Ahvaz, Iran. Therefore, this present cross-sectional study was conducted in 13 hospitals Ahvaz city. There are 3000 registered nurses in in the 13 hospitals making up the sampling frame of the study. A total of 450 of these nurses were randomly recruited based on the exclusion and inclusion criteria. Blood tests as well as anthropometric measurements were taken and all the nurses were given the study questionnaire. Eventually, 417 out of the 450 nurses continued and completed the project (responsive rate 92.66%). The mean age of the participants was 35±7.78 year, and the mean years of job experiences were 9.58±6.98 years. About 10.8% of the participants had metabolic syndrome based on the ATPIII-definition. Meanwhile, abdominal obesity was observed in 36.7% of the respondents (n=153). The prevalence of hypertension, high fasting blood glucose, high triglyceride and low HDL-cholesterol were 5.5%, 3.6%, 19.9%, and 22.1%, respectively. Only about one percent of the nurses had all the four metabolic syndrome components. High-level cholesterol was found in 25 % of the respondents. The prevalence of Low HDLcholesterol concentrations and the high LDL-cholesterol were 67.9% and 47.2% respectively. The prevalence of high triglyceride level was 22%. The prevalence of high-level fasting glucose (6.10-6.93mmo/l) was 3.6%. A total of 142 (34.1%) respondents was classified in the 1sttertile occupational stress category (Score: 178-247), 134 (32.1%) were classified in the 2ndtertile category (Score: 248-270) and 141 (33.8%) were classified in the 3rdtertile category (271-354) as well. The majority of nurses had either low (188 or 44.6%) or high (78 or 18.7%) physical activity levels. About 153 (36.7%) had moderate physical activity. Body mass index (χ2=6.013, p=0.049) and fasting plasma glucose (F=9.452, p=0.009) were significantly related to occupational stress respectively. In addition, total cholesterol was significantly related to occupational stress (χ2=27.886, p=0.001). Moreover the LDL cholesterol (χ2=14.255, p=0.007), healthy diet (χ2=52.248, p=0.001) western diet (χ2=13.718, p=0.008; F=566.530,p=0.001), traditional diet, were significantly related to occupational stress respectively. In addition, exposure to smoking was significantly related to metabolic syndrome (χ2=8.055, p=0.005). A significant association was found between age with occupational stress, (ß=0.266, S.E=0.278,p=0.001). A significant association was seen among nurses who was exposed to smoke with occupational stress, (ß=-0.104, S.E=0.001, p=0.034). A strong association between systolic blood pressure (ß=0.245, S.E=2.417, p=0.001), diastolic blood pressure (ß=0.204, S.E=0.180, p=0.001) and sex; (ß=0.128, S.E=1.876,p=0.015) was seen respectively. Beside results showed association between fasting plasma glucose with age (ß=204 S.E=0.180, p=0.001and education (ß=-0.112, S.E=4.183, p=0.034) respectively. HDL cholesterol showed significant association with sex (ß=-0.075, S.E=0.055, p=0.032), and marital status (ß=0.128, S.E=0.724, p=0.015) respectively as well. Triglyceride with sex (ß=0.118, S.E=12.126,p=0.017); and marital status (ß=-0.164, S.E=6.635, p=0.001) showed significant association respectively. Similarly, triglyceride was significantly associated with education level (ß=-0.152 S.E=11.685, p=0.003), as well as physical activity moderate (ß=0.125, S.E=0.001, p=0.041) and leisure time recreation moderate (travel) (ß=0.113 S.E=0.006, p=0.042). Likewise waist circumference had significant association with age, sex, marital status, years of job experience, education, high physical activity, and healthy diet (p<0.05). Additionally, a structural equation modeling analysis was performed to test the proposed mediation model. The model showed no effects of occupational stress factors on metabolic syndrome through lifestyle behavior. In conclusion, lifestyle behavior did not mediate the relationships between occupational stress and metabolic syndrome.